2013
DOI: 10.1186/1471-2407-13-289
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of normal and malignant breast tissue show CD44high/CD24lowphenotype as a predominant stem/progenitor marker when used in combination with Ep-CAM/CD49f markers

Abstract: BackgroundAccumulating evidence supports cancer to initiate and develop from a small population of stem-like cells termed as cancer stem cells (CSC). The exact phenotype of CSC and their counterparts in normal mammary gland is not well characterized. In this study our aim was to evaluate the phenotype and function of stem/progenitor cells in normal mammary epithelial cell populations and their malignant counterparts.MethodsFreshly isolated cells from both normal and malignant human breasts were sorted using 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 31 publications
1
61
0
3
Order By: Relevance
“…In a previous study by Al-Hajj et al (2003), primary cells contained a sub-population of CD44 + CD24 -cells with high tumourigenicity (Al-Hajj et al, 2003). However, the possibility that the primary cells expressing CD44 + CD24 -were not all BCSCs appears likely (Ghebeh et al, 2013;Mannello, 2013). In a recent study, Ghebeh et al (2013) clearly demonstrated that both normal breast tissue and breast cancer tissue harboured CD44 + CD24 -cells (Ghebeh et al, 2013).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In a previous study by Al-Hajj et al (2003), primary cells contained a sub-population of CD44 + CD24 -cells with high tumourigenicity (Al-Hajj et al, 2003). However, the possibility that the primary cells expressing CD44 + CD24 -were not all BCSCs appears likely (Ghebeh et al, 2013;Mannello, 2013). In a recent study, Ghebeh et al (2013) clearly demonstrated that both normal breast tissue and breast cancer tissue harboured CD44 + CD24 -cells (Ghebeh et al, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…In a recent study, Ghebeh et al (2013) clearly demonstrated that both normal breast tissue and breast cancer tissue harboured CD44 + CD24 -cells (Ghebeh et al, 2013). They also suggested that BCSCs would be enriched in the CD44 + CD24 -cells if they were combined with the CD49f + phenotype (Ghebeh et al, 2013). CD49f was also determined as a marker of BCSCs in previous studies (Meyer et al, 2010;Yu et al, 2012 However, Medium D and Medium M also supported stromal cell proliferation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Normal breast luminal cells were obtained from the same tissues and were cultured as previously described (51).…”
Section: Methodsmentioning
confidence: 99%
“…While they do not initiate tumor formation, they have been postulated to drive the growth of the tumor mass [23]. It has been suggested that CSCs may derive from normal progenitor counterparts, because the CD44+/CD24-markers [24] which, with the aldehyde dehydrogenase enzyme (ALDH) [25] currently define CSCs, have been used to isolate cells with progenitor activity from normal human breast epithelial cells [26]. These observations highlight the fact that tight regulation of cell fate determination is critical for normal breast development, and that disrupted cell fate decisions are implicated in breast cancer.…”
Section: Abbreviationsmentioning
confidence: 99%